Jellyfish collagen hydrolysate-loaded niosome for topical application: formulation development, antioxidant and antibacterial activities - Ab Aziz, Noor Atikah; Salim, Norazlinaliza; Saari, Nazamid; Md. Yusoff, Fatimah; Zarei, Mohammad (Universiti Malaysia Terengganu, 2022)
Vesicular carrier system, niosome, has become an attractive delivery system for active ingredients in cosmetics and pharmaceuticals. This study aims to prepare a niosome formulation containing collagen hydrolysate extracted from local jellyfish (Rhopilema hispidum) with promising antioxidant and antibacterial properties. Niosomes, which are composed of a mixture of non-ionic surfactants, was prepared by using coacervation and sonication techniques optimized using a D-optimal mixture experimental design (MED) to obtain a small particle size. The particle size of the niosome obtained was 111.2 nm with a polydispersity index (PDI) value of 0.256 and a zeta potential value of −6.62 mV. Transmission Electron Microscopy (TEM) study showed the formation of spherical bilayer vesicle with a size correlating well with Zetasizer analysis. The stability of the niosome formulation was studied over a 60-day period, during which changes in particle size from 104.5 to 386.5 nm were observed. The results showed no phase separation or creaming. Niosome obtained from this study was shown to exhibit antioxidant (65.9% DPPH scavenging activity and 34.6% metal chelating activity) and exhibited inhibitory activity against Staphylococcus aureus (up to 98.8%). The optimized niosome might be suitable for topical application.